Mycovirus Hunting Revealed the Presence of Diverse Viruses in a Single Isolate of the Phytopathogenic Fungus Diplodia seriata From Pakistan - Khan, Haris Ahmed; Telengech, Paul; Kondo, Hideki; Bhatti, Muhammad Faraz; Suzuki, Nobuhiro (Frontiers in cellular and infection microbiology, 2022)
Diplodia seriata in the family Botryosphaeriaceae is a cosmopolitan phytopathogenic fungus and is responsible for causing cankers, fruit rot and leaf spots on economically important plants. In this study, we characterized the virome of a single Pakistani strain (L3) of D. seriata . Several viral-like contig sequences were obtained via a previously conducted next-generation sequencing analysis. Multiple infection of the L3 strain by eight RNA mycoviruses was confirmed through RT-PCR using total RNA samples extracted from this strain; the entire genomes were determined via Sanger sequencing of RT-PCR and RACE clones. A BLAST search and phylogenetic analyses indicated that these eight mycoviruses belong to seven different viral families. Four identified mycoviruses belong to double-stranded RNA viral families, including Polymycoviridae , Chrysoviridae , Totiviridae and Partitiviridae , and the remaining four identified mycoviruses belong to single-stranded RNA viral families, i.e., Botourmiaviridae , and two previously proposed families “ Ambiguiviridae ” and “ Splipalmiviridae ”. Of the eight, five mycoviruses appear to represent new virus species. A morphological comparison of L3 and partially cured strain L3ht1 suggested that one or more of the three viruses belonging to Polymycoviridae , “ Splipalmiviridae ” and “ Ambiguiviridae ” are involved in the irregular colony phenotype of L3. To our knowledge, this is the first report of diverse virome characterization from D. seriata .